Long-Term Clinical Outcome After Alcohol Septal Ablation and Its Periprocedural Predictive Factors in Japan ― A Retrospective Observational Study - Ono, Sachiyo; Kadota, Kazushige; Ohya, Masanobu; Sawayama, Yuichi; Kubo, Shunsuke; Tanaka, Hiroyuki; Nakagawa, Yoshihisa; Maruo, Takeshi (Circulation Journal, 2023)
Background: Evidence is limited regarding long-term clinical outcomes after alcohol septal ablation (ASA) for patients with hypertrophic obstructive cardiomyopathy and its periprocedural predictive factors in Japan.Methods and Results: This retrospective observational study included 44 patients who underwent ASA between 1998 and 2022 in a single center. We evaluated the periprocedural change in variables and long-term clinical outcomes after the procedure. The primary outcome was a composite of cardiovascular death or hospitalization for heart failure. The secondary outcome was all-cause death. Using multivariable Poisson regression with robust error variance, we predicted underlying periprocedural factors related to primary outcome development. ASA decreased the median pressure gradient at the left ventricular outflow tract from 88 to 33 mmHg and reduced moderate or severe mitral regurgitation (MR), present in 53% of patients before ASA, to 16%. Over a median 6-year follow-up, the cumulative incidence of the primary outcome at 5 and 10 years was 16.5% and 25.6%, respectively. After multivariable analysis, moderate or severe MR after ASA was significantly associated with the primary outcome (relative risk 8.78; 95% confidence interval 1.34–57.3; P=0.024). All-cause mortality after ASA was 15.1% and 28.9% at 5 and 10 years, respectively.Conclusions: This study presents long-term clinical outcomes after ASA in Japan. Moderate or severe MR after ASA was significantly associated with the composite of cardiovascular death or hospitalization for heart failure.